Design, Synthesis, Radiosynthesis and Biological Evaluation of Fenretinide Analogues as Anticancer and Metabolic Syndrome‐Preventive Agents. (9th July 2020) - Patruno, Ilaria; Thompson, Dawn; Dall'Angelo, Sergio; Windhorst, Albert D.; Vugts, Danielle J.; Poot, Alex J.; Mody, Nimesh; Zanda, Matteo
Abstract: Fenretinide (4‐HPR) is a synthetic derivative of all‐ trans ‐retinoic acid (ATRA) characterised by improved therapeutic properties and toxicological profile relative to ATRA. 4‐HPR has been mostly investigated as an anti‐cancer agent, but recent studies showed its promising therapeutic potential for preventing metabolic syndrome. Several biological targets are involved in 4‐HPR's activity, leading to the potential use of this molecule for treating different pathologies. However, although 4‐HPR displays quite well‐understood multitarget promiscuity with regards to pharmacology, interpreting its precise physiological role remains challenging. In addition, despite promising results in vitro, the clinical efficacy of 4‐HPR as a chemotherapeutic agent has not been satisfactory so far. Herein, we describe the preparation of a library of 4‐HPR analogues, followed by the biological evaluation of their anti‐cancer and anti‐obesity/diabetic properties. The click‐type analogue 3 b showed good capacity to reduce the amount of lipid accumulation in 3T3‐L1 adipocytes during differentiation. Furthermore, it showed an IC50 of 0.53±0.8 μM in cell viability tests on breast cancer cell line MCF‐7, together with a good selectivity (SI=121) over noncancerous HEK293 cells. Thus, 3 b was selected as a potential PET tracer to study retinoids in vivo, and the radiosynthesis of [ 18 F]3b was successfully developed. Unfortunately, the stability of [ 18 F]3b turned out to be insufficient to pursue imaging studies. Abstract : PET potential ? Fenretinide analogues have been designed and synthesised in a single‐step amide coupling or a click‐chemistry approach. These compounds were evaluated in vitro for their anti‐cancer and their anti‐obesity/diabetic properties. Based on the results, analogue 3 b was selected as potential PET imaging tracer, and [ 18 F]3b was radiosynthesised. Unfortunately, it was insufficiently stable for in vivo imaging.